2009
DOI: 10.1002/ajmg.b.30900
|View full text |Cite
|
Sign up to set email alerts
|

Convergent genome wide association results for bipolar disorder and substance dependence

Abstract: Twin studies document substantial heritability for substance dependence and bipolar disorder [Shih et al. (2004); Uhl et al. (2008a)]. Individuals with bipolar disorder display substance use disorders at rates that are much higher than those in the general population [Krishnan (2005)]. We would thus predict: 1) substantial overlap between different genome wide association (GWA) studies of bipolar disorder 2) significant overlap between results from bipolar disorder and substance dependence. Recent GWA studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 26 publications
(48 reference statements)
1
44
1
1
Order By: Relevance
“…[18][19][20]44,45 Protocadherins and other cadherins have also been studied as candidate risk genes, but generally in small samples (o100 patients) of schizophrenia, bipolar disorder and OCD patients. [46][47][48][49][50][51][52][53][54][55] In addition, some cadherins have been specifically identified in genome-wide association scans of ADHD, addiction and neuroticism personality features. [56][57][58] Of related interest, variants in CDH2 and other cadherins have been widely found to CDH2 variants in OCD and TD PR Moya et al be associated with various cancers 16,59,60 and, specifically, upregulated CDH2 has been associated with transepithelial spreading of melanoma and pancreatic cancer together with rapid recurrence of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20]44,45 Protocadherins and other cadherins have also been studied as candidate risk genes, but generally in small samples (o100 patients) of schizophrenia, bipolar disorder and OCD patients. [46][47][48][49][50][51][52][53][54][55] In addition, some cadherins have been specifically identified in genome-wide association scans of ADHD, addiction and neuroticism personality features. [56][57][58] Of related interest, variants in CDH2 and other cadherins have been widely found to CDH2 variants in OCD and TD PR Moya et al be associated with various cancers 16,59,60 and, specifically, upregulated CDH2 has been associated with transepithelial spreading of melanoma and pancreatic cancer together with rapid recurrence of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…BP WalssBass et al, 2006;Thomson et al, 2007;Georgieva et al, 2008] (assoc) D (unipolar depression) [Bertram et al, 2007] BP [Cichon et al, 2001;Park et al, 2004] 6096 RORB (RAR-related orphan receptor beta) BP [Baum et al, 2008;Johnson et al, 2009] (assoc)…”
Section: Genetic Risk Prediction Panel and Scoringmentioning
confidence: 99%
“…One is that there could be shared genetic and environmental vulnerabilities among people with SUDs and BD. The presence of BD among probands was associated with a higher prevalence of SUDs among family members in an association study (Biederman et al, 2000) while a genome-wide association study has identified shared genes of risk between BD and SUD (Johnson et al, 2009). Such shared risk factors may include impulsivity and a propensity for risk-taking, which have been associated specifically with persons with bipolar disorder, especially when not taking antipsychotic medication (Reddy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%